Among the Hidden - Haddix, Margaret Peterson; Nielsen, Cliff (New York, NY Aladdin Paperbacks, 1998)
In a future where the Population Police enforce the law limiting a family to only two children, Luke has lived all his twelve years in isolation and fear on his family's farm, until another "third" convinces him that the government is wrong.
"First Aladdin Paperbacks edition March 2000"--T.p. verso.
800L
88691
Keywords: Birth control; Social isolation